Possibilities and Challenges for a New University - Barrantes Montero, Luis Guillermo (2024)
This is a reflection on the possibilities of building a new university—not changing the current model of the university but renewing it. The extended implantation of imported, acritical, and decontextualized pedagogies has led to the challenge of finding alternatives based on the acquisition, analysis, and production of knowledge in situ, that is, bridging the knowledge of the global epistemological community and meaningful pedagogies for local contexts. To that aim, the role of the university in the era of information is discussed along with the effect of the irruption in Latin America of the Bologna Process.